Pengaruh Komunikasi Pemasaran dan Harga terhadap Keputusan Pembelian di PT. Warna Abadi Mitra Bersama Makassar - Natasya Jane Veronica M; Muh. Akbar; Muhammad Yusuf AR (MUKASI: Jurnal Ilmu Komunikasi, 2024)
This study aims to determine the effect of marketing communication and price on purchasing decisions at PT Warna Abadi Mitra Bersama Makassar. And to analyze which variable has a more dominant influence on purchasing decisions at PT Warna Abadi Mitra Bersama Makassar. This research was conducted in Makassar city with a sample size of 383 respondents. The data analysis used is descriptive to explain the research data. Meanwhile, to analyze quantitative data, multiple linear regression analysis was used with the SPSS version 27 program. The results showed that marketing communication and price simultaneously influenced purchasing decisions at PT Warna Abadi Mitra Bersama Makassar, with a coefficient of determination R square of 83.2%, and the remaining 16.8% was influenced by other variables outside this study. Partially, the marketing communication and price variables have a significant and positive effect on purchasing decisions at PT Warna Abadi Mitra Bersama Makassar. This study also shows that the price variable is the most dominant factor in influencing purchasing decisions at PT Warna Abadi Mitra Bersama Makassar with a t-value of 23.553> t-table 1.966.